Cidades inteligentes e proteção de dados: uma análise do caso da cidade do recife para otimização do marco regulatório atual. - Cavalcanti Neto, Gabriel de Oliveira (2024)
The concept of smart city is related to the existence of information and communication technology systems for the development of innovative actions and the creation of new cities. However, the phenomenon has implications in the legal field that have not been properly analyzed to date, such as privacy and data protection. Given this, the dissertation analyzes whether the LGPD is capable of controlling possible threats to personal privacy in smart cities, as well as data processing in the city of Recife. To this end, the study seeks legislation pertinent to public policies and data protection in the city of Recife, carrying out a multi/transdisciplinary systematic review on the topic of smart cities, in order to point out possible ways to improve citizens' data protection due to of privacy threats caused by smart cities. Methodologically, this is a single case study in the city of Recife-PE, qualitative in nature, with data collected through documentary and bibliographic research. Legal documents that contribute to smart governance public policies in Recife-PE, experiences involving actors and practices in the city and how Information Management guarantees the protection of citizens' data are analyzed.